Enhanced self-cleaning performance on hydrophobic glass surfaces using hydrophilic dagger features coated with silica nanoparticles - Abeywardena, Madupa; Zimmermann, Thomas; Xu, Qian Feng; Loebmann, Peer; Mandel, Karl; Stauch, Claudia; Lyons, Alan (Solar Energy Materials and Solar Cells, 2025)
Accumulated dust on solar cover glass reduces transmittance, leading to decreased energy efficiency of photovoltaic (PV) modules. Hydrophobic coatings on solar cover glass have been shown to provide anti-soiling properties when exposed to a condensing environment (e.g. dew). The addition of hydrophilic features along the top edge of the hydrophobic coated glass enhances condensation rates and can be used to achieve self-cleaning of the surfaces. However, to date, relatively long times have been required to clean the surfaces. In this study, we developed a new design for hydrophilic features that reduce the time required to clean the surface in laboratory tests as measured by laser scanning microscopy, optical photographs and UV–vis spectroscopy. The dagger-shaped features improve self-cleaning performance by a combination of three factors: a silica nanoparticle (NP) hydrophilic coating which enhances condensation rate due to a low water contact angle (WCA) and nano-scale porosity; the stepwise transition from the low WCA silica NP region to the high WCA silanized hydrophobic region via a bare glass transition zone; and the pointed shape of the hydrophobic dagger features which further minimizes the barrier for transport of droplets from the condensing region to the high-mobility, hydrophobic, region of the surface. The hydrophilic silica nanoparticle-coated dagger features not only improve the self-cleaning efficiency of the hydrophobic surfaces but also increase the overall amount of water harvested. Such coating designs provide an effective approach to reducing maintenance costs as well as increasing the overall energy output of PV panel
CRIS-Team Scopus Importer:2025-02-17
Keywords: Photovoltaic glass; Anti-soiling; Self-cleaning; Water harvesting; Hydrophilic; Hydrophobic; Nanoparticles